Small molecule inhibitors of Mdm2 E3 ubiquitin ligase activity - Dickens, Michael (2011)
Half of cancers retain wild type p53 but have alterations in the pathways involved in p53 regulation. Murine double minute 2 (Mdm2) regulates p53 by acting as an E3 ubiquitin ligase, which tags p53 for degradation through the proteasome. A small molecule inhibitor, a 5-deazaflavin analogue, has previously been identified by high throughput screening to inhibit Mdm2 E3 ubiquitin ligase activity, thereby reactivating apoptotic function of p53 selectively in cancer cells.